The endocannabinoid system and breathing - Wiese, Beth M.; Alvarez Reyes, Angelica; Vanderah, Todd W.; Largent-Milnes, Tally M. (Frontiers in Neuroscience, 2023)
Recent changes in cannabis accessibility have provided adjunct therapies for patients across numerous disease states and highlights the urgency in understanding how cannabinoids and the endocannabinoid (EC) system interact with other physiological structures. The EC system plays a critical and modulatory role in respiratory homeostasis and pulmonary functionality. Respiratory control begins in the brainstem without peripheral input, and coordinates the preBötzinger complex, a component of the ventral respiratory group that interacts with the dorsal respiratory group to synchronize burstlet activity and drive inspiration. An additional rhythm generator: the retrotrapezoid nucleus/parafacial respiratory group drives active expiration during conditions of exercise or high CO2. Combined with the feedback information from the periphery: through chemo- and baroreceptors including the carotid bodies, the cranial nerves, stretch of the diaphragm and intercostal muscles, lung tissue, and immune cells, and the cranial nerves, our respiratory system can fine tune motor outputs that ensure we have the oxygen necessary to survive and can expel the CO2 waste we produce, and every aspect of this process can be influenced by the EC system. The expansion in cannabis access and potential therapeutic benefits, it is essential that investigations continue to uncover the underpinnings and mechanistic workings of the EC system. It is imperative to understand the impact cannabis, and exogenous cannabinoids have on these physiological systems, and how some of these compounds can mitigate respiratory depression when combined with opioids or other medicinal therapies. This review highlights the respiratory system from the perspective of central versus peripheral respiratory functionality and how these behaviors can be influenced by the EC system. This review will summarize the literature available on organic and synthetic cannabinoids in breathing and how that has shaped our understanding of the role of the EC system in respiratory homeostasis. Finally, we look at some potential future therapeutic applications the EC system has to offer for the treatment of respiratory diseases and a possible role in expanding the safety profile of opioid therapies while preventing future opioid overdose fatalities that result from respiratory arrest or persistent apnea.